Analisis Problem Based Learning Berbantu LKPD (Lembar Kerja Peserta Didik) Pada Tema 7 Subtema 2 Pembelajaran 2 Kelas III - Alfiani, Nurul; Musyafanah, Qoriati; Listyarini, Ikha (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2023)
Effective and innovative learning methods are crucial to ensure that students can gain deep understanding and develop the necessary skills. Research conducted a descriptive research basic qualitative approach. This research was at SDN Kalicari 01 Semarang with 27 students. The data collection technique in this research is triangulation. This LKPD teaching material will run with the help of the Problem Based Learning model. Learning can run effectively, this model requires students to be active in solving problems in learning. Based on the research that has been done by researchers. The utilization of LKPD based on the PBL as teaching material has a positive effect in increasing student activeness. LKPD based on PBL model is feasible to use as teaching material in schools, because the use of PBL-based LKPD in the learning process can help students understand the material so that the success of the teaching and learning process is achieved.